2015
DOI: 10.5999/aps.2015.42.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Negative Pressure Wound Therapy of Chronically Infected Wounds Using 1% Acetic Acid Irrigation

Abstract: BackgroundNegative-pressure wound therapy (NPWT) induces angiogenesis and collagen synthesis to promote tissue healing. Although acetic acid soaks normalize alkali wound conditions to raise tissue oxygen saturation and deconstruct the biofilms of chronic wounds, frequent dressing changes are required.MethodsCombined use of NPWT and acetic acid irrigation was assessed in the treatment of chronic wounds, instilling acetic acid solution (1%) beneath polyurethane membranes twice daily for three weeks under continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…After 2-12 days, P. aeruginosa was eliminated [236]. Using NPWTi with 1% AA ( n = 3; instillation of 30 mL twice daily for 3 weeks, no control), the number of pathogens (MRSA, Gram-negative) was significantly reduced ( n = 2) or eliminated; this was associated with improved healing and a shift from highly basic pH to a weak basic or neutral pH [240] (Table 12). …”
Section: Future Perspectivesmentioning
confidence: 99%
“…After 2-12 days, P. aeruginosa was eliminated [236]. Using NPWTi with 1% AA ( n = 3; instillation of 30 mL twice daily for 3 weeks, no control), the number of pathogens (MRSA, Gram-negative) was significantly reduced ( n = 2) or eliminated; this was associated with improved healing and a shift from highly basic pH to a weak basic or neutral pH [240] (Table 12). …”
Section: Future Perspectivesmentioning
confidence: 99%
“…Acetic acid has been investigated to prevent biofilms in the dental 41 , food 42 , and wound health 43 contexts. However, contact times are measured in hours, and there is less existing research relevant to cleaning storage containers.…”
Section: Discussionmentioning
confidence: 99%
“…As well as preventing infection and decreasing the bacterial load, NPWT has demonstrated a wide variety of merits in the treatment of complex wound defects. Previous studies have reported that NPWT is able to decrease wound size, maintain a moist atmosphere for wound healing, reduce edema and assist with the closure of areas not fully closed in the wound, also termed dead cavities (8,22). Notably, microscopically NPWT is able to promote granulation, vascularization, epithelialization and the synthesis of fibrin within the wound (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies regarding the use of NPWT primarily concern traumatic wounds with or without infection, and the most frequently used pressure is -80 to -125 mmHg (31). In cases with fragile wound edges, low perfusion, poor tolerability or skin grafts, a minor pressure (<125 mmHg) is often attempted (8). Furthermore, negative pressure protocols are typically used at one of two settings, namely, continuous or intermittent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation